2020
DOI: 10.3390/agronomy10030418
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tobacco Plant on Macronutrient Levels in Sandy Soils

Abstract: Tobacco (Nicotiana tabacum L.) is associated with great uptake of soil macronutrients. Following the need to understand the macronutrients levels before and after tobacco cultivation, research was conducted in loamy sand soil of Sikonge, Urambo, and sand soil of Tabora, Tanzania. The initial macronutrients levels in the soil were compared with those measured after unfertilized and fertilized tobacco. Results showed that unfertilized tobacco plant influences the increase of nicotine to the rhizosphere, the macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
(26 reference statements)
1
16
0
1
Order By: Relevance
“…In this special issue, Pellegrino et al [11] demonstrated that soil inoculated with Rhizophagus irregularis at planting increased micronutrient uptake in wheat grain, although there was significant variability between wheat genotypes. Lisuma et al [12] reported that under tobacco production, soil P, K, Mg, and S decreased while N and Ca increased, likely due to an increase in nicotine deposition in the rhizosphere. Oo et al [13] assessed the effect of dipping rice seedlings in a P-enriched solution before transplanting.…”
Section: Plant Factorsmentioning
confidence: 99%
“…In this special issue, Pellegrino et al [11] demonstrated that soil inoculated with Rhizophagus irregularis at planting increased micronutrient uptake in wheat grain, although there was significant variability between wheat genotypes. Lisuma et al [12] reported that under tobacco production, soil P, K, Mg, and S decreased while N and Ca increased, likely due to an increase in nicotine deposition in the rhizosphere. Oo et al [13] assessed the effect of dipping rice seedlings in a P-enriched solution before transplanting.…”
Section: Plant Factorsmentioning
confidence: 99%
“…The present study also indicated that NPK and CAN had an enormous influence on the increases of the extractable Zn solubility in the studied soils, similar to the observations reported in other related studies [ 8 , 22 ]. Tobacco plants release nicotine into the soil environment, which is also acidic, and hence increase the solubility of many micronutrients, thereby making them readily available to the tobacco plant [ 10 ]. The trends of these micronutrients in soils will also have varying impacts on the overall soil health and fertility and may affect the yields of the subsequent crops [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SOM increases the uptake of micronutrients by the plants through increase in their solubility and the resultant nature of exchangeable forms [ 7 ]. Whereas a study conducted by Lisuma et al [ 10 ] described the effect of nicotine released by tobacco on the availability of the extractable macronutrients in the sandy soils, the present study addressed the effect of the same nicotine on the solubility of the extractable micronutrients in the same soils. The two studies used the same experimental design and the soils for evaluating the levels of macronutrients and micronutrients were collected from the same plots.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nitrogen-containing compounds in flue-cured NTL leaves include protein, alkaloids, etc. Nitrogen-containing compounds not only affect the characteristics of leaves and determine economic output, but also have an important impact on the quality of leaves [60]. Alkaloids are a class of secondary metabolites that contain nitrogen.…”
Section: Discussionmentioning
confidence: 99%